2009
DOI: 10.1002/pbc.22249
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and parenchymal thickness/kidney length ratio in Wilms tumor survivors

Abstract: CysC levels may be elevated in people with normal GFR. Hypertrophy of a single kidney increases with deteriorating kidney function. PT/KL should be verified in future studies as a sonographic marker of kidney impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Fischbach et al proposed a value of 0.95 mg/dl as a cut-off value and this is the highest value published in the literature [13]. According to Stefanowicz et al, 42% of individuals after treatment of Wilms’ tumour had a serum concentration of cystatin C that was elevated to over 0.95 mg/dl [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Fischbach et al proposed a value of 0.95 mg/dl as a cut-off value and this is the highest value published in the literature [13]. According to Stefanowicz et al, 42% of individuals after treatment of Wilms’ tumour had a serum concentration of cystatin C that was elevated to over 0.95 mg/dl [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophy of a solitary kidney [length or volume of kidney over 2SD (standard deviation of reference value)] in WTS was observed in 50-88% of individuals (9,37,38). Mean value of renal length was 128 ± 14% of the reference value.…”
Section: %mentioning
confidence: 95%
“…In one study, correlation between microalbuminuria and renal volume was observed (40). The parenchymal thickness/kidney length ratio correlated with the deterioration of renal function (cystatin C serum concentration) (38). Currently, in light of the definition of CKD for individuals with the risk of deterioration of kidney function, it is essential not only to assess GFR but also to establish the presence of structural and functional markers of kidney damage.…”
Section: %mentioning
confidence: 99%
“…Il s'agit d'une mauvaise adaptation, source d'hyperfiltration entraînant à long terme l'apparition d'une microalbuminurie, puis le développement d'une glomérulosclérose, de dommages interstitiels avec fibrose, qui risquent progressivement d'évoluer vers une insuffisance rénale (figure 1) [22,23]. Une étude récente de Stefanowicz et al tend à confirmer que l'hypertrophie, reflet de cette adaptation inadéquate, est corrélée à long terme à une altération de la fonction rénale [24]. La survenue d'une microalbuminurie, reflet de l'hyperfiltration glomérulaire postnéphrectomie, est mal décrite avec des évaluations très hété-rogènes rapportant une incidence de 5 à 84 % de cette complication au-delà de 5 ans post-néphrectomie [20,25] [29].…”
Section: Néphrectomieunclassified